Teaching Question Words For Adult Learning By Using The Pictures Of Giant Buildings As A Teaching Media - Ali Amran (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2015)
This Study aims to investigate and improve the learners mistakes in applying question word : what, when, where, why, who, whose, which and how through the pictures of a gient buildings.